Intellectual property law in India - Narayana, P.S (Hyderabad, 2010)
The present book "Intellectual Property Law in India" is a short and brief commentary on the subject the important enactments dealing with this subject can be enumerated in brief as follows-- (1) Patents Act, (2) Trademarks Act, (3) Copyright Act and (4) Designs Act.
Keywords: Intellectual property act